Case Study : KZ Aneka Kerepek Enterprise / Hadi Zami Hasnor - Hasnor, Hadi Zami (2020)
For this case study, I have interviewed Mr Kasim the owner of KZ Aneka Kerepek Enterprise, a sole proprietorships business that sells variety types of ‘kerepek’ and ‘Muruku’ in Jalan Pahang, Tapah, Perak. The business has been operated successfully for about 9 years. However, the result from the interview session, we have identified three main problems that currently affect the business operation and will give long term effects in future. Some of the problem arose from the external environment, for instance the competition with business rivals around the same area. KZ Aneka Kerepek Enterprise need to put a lot of effort to get the customers around Tapah area since there are a lot of other Kerepek Retailers around Tapah. Moreover, there is also a Muruku Factory near Tapah that can produce Muruku products in a large quantities, low cost and short time. On the other hand, the problem also arose from the internal factor such as lack of transaction recording for their profit or loss in business. Since the owner of KZ Aneka Kerepek Enterprise does not have basic knowledge about accounting, he only records the daily sales amount and do not make a proper savings. Hence, it is hard for him to decide the profit or loss from his business operation. On top of that, the company also faces the problem to store his inventory properly. This is because his products will get spoiled easily in almost 3 weeks and this problem will lead to the business loss since he cannot sell the scrap products. In this case study, I will discuss all these problems and suggest the best alternative solutions that KZ Aneka Kerepek Enterprise can be afford so they can become better for the future.